Comparing Two Language Version Of Science Achievement Tests Using Differential Item Functioning - Ong , Saw Lan (Penerbit Universiti Sains Malaysia, 2007)
At the national level, the Ministry of Education in Malaysia assesses the achievement of primary school students in reading and writing, mathematics and science. The results of the assessments are used for selection decisions as well as for grading students. Since the implementation of the new language policy of teaching science and mathematics in English, both Malay and English have been used as the language of assessment. The validity of interpretation for tests results across different language version is an important issue that needs to be investigated. Translating a test from a source language to a target language does not necessarily produce two psychometrically equivalent tests. The purpose of this study is to identify item(s) in translated achievement tests that may function differently across languages. Differential Item Functioning (DIF) analysis is useful to reveal items with psychometric characteristics that have been altered by the translation. Two statistical analyses were conducted to identify and evaluate DIF item(s). The simultaneous item bias test (SIBTEST), a nonparametric statistical method of assessing DIF in an item is used. The result obtained is then compared with the oneparameter logistic model, analyze using BILOG-MG V3.0 in assessing DIF in translated items. Both statistical analyses identified approximately 50% of the science items displayed DIF. This result suggests that substantial psychometric differences exist between the two language versions of the science test at the item level.